Existing data to measure African trade - Mitaritonna, Cristina; Traoré, Fousseini (International Food Policy Research Institute, 2017)
One finds a broad consensus in the literature regarding the lack of good information on trade in Africa, particularly intraregional trade. This paper attempts to identify gaps and remedies in measuring and tracking trade in Africa. We review the major international and regional databases that track trade in Africa, identifying the gaps therein. We also review the studies that have attempted to track informal trade between African countries, and we look at the major ongoing initiatives to track such informal trade. It appears that both international and regional databases suffer from a lack of reporting or from faulty reporting of African trade statistics. Informal trade flows pose an ongoing problem when measuring intraregional trade, although actual border-monitoring initiatives ongoing in selected countries constitute an interesting option for their quantification. When no direct monitoring method is available, estimating gravity equations represents an alternative with which to measure the potential trade between two partner countries, giving us an estimate of missing trade. A final avenue consists of estimating unregistered trade via national accounts data by comparing consumption, production, and declared trade.